Measuring effective labor regulation in the less developed world: Recent advances and challenges ahead - Lucas Ronconi; Steven Raphael (Institute of Labor Economics (IZA), 2024)
This paper reviews recent efforts in social science to analyze labor enforcement in low-andmiddle income countries (LMIC) and inform policy debates. Despite the existing limitations, the empirical evidence suggests that: 1) Enforcement is quite low in LMIC; there are fewer inspectors and inspections, lower penalties, and less trust in the judiciary compared to developed countries. 2) Increasing enforcement produces more compliance with little job destruction, although there is substantial debate and heterogeneity across countries. 3) Countries with more protective labor codes tend to enforce less. 4) Countries that become more open to trade also tend to enforce less. However, trade agreements with special clauses protecting workers can promote higher labor enforcement. 5) Inspection agencies in LMIC tend to focus their efforts on formal firms, leaving informal firms out of the radar which implies that the most vulnerable workers are usually excluded. 6) The constituency base of the government shapes labor enforcement, wherein labor-based governments devote more resources to inspection, although this is a debated issue. 7) Labor unions help promote enforcement, although in LMIC they can displace public inspections from small informal firms to larger formal firms because there is where labor unions members work. 8) Autonomous and professional bureaucracies do more labor enforcement presumably because they internalize the long-run benefits of enforcing the law and allow inspectors to accumulate experience.
Keywords: J88; K42; O43; P48; 330; labor; inspections; enforcement; informality; development; judiciary